THE CONDITION AND DISTRIBUTION OF CORAL REEFS IN THE SHALLOW WATERS OF NIRWANA BEACHES SUBDISTRICT OF BUNGUS TELUK KABUNG OF PADANG CITY OF WEST SUMTERA PROVINCE - Rivaldi Ananda Dwi Putra; Thamrin '; Yusni Ikhwan Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Nirwana beaches water is well known as recreation and harbor. Such condition apparently brings negative impacts to marine life. Corals are considered as the major component of coral reef ecosystems whose condition is influenced by environmental condition. The aim of this study is to observe the general condition of coral reefs and the distribution of stony corals in Nirwana Beaches. The study was carried out Januari until May 2017 by taking 5 stations. The method used was Line Transect and coral identification using Coral Finder. The result indicates that generally the condition of coral reef was categorized as good condition, the coral cover averaging at 51.66 %. There were 109 organism of corals found, divided into 5 species. The morisita index value of 1.764 indicates that corals are distributed in groups. The highest frequency of occurrence of coral species by Porites. Human activities cause damage to coral reef ecosystems.Keywords: Corals, Coral Cover, Distribution, Nirwana Beaches.